Effects of a single dose of oral estrogen on left ventricular diastolic function in hypertensive postmenopausal women with diastolic dysfunction - (:unkn) unknown (ELSEVIER SCIENCE INC, 2000)
Objective: To evaluate the acute effects of a single dose of oral estrogen on left ventricular diastolic function in hypertensive postmenopausal women with diastolic dysfunction. Design: Prospective, double-blind, placebo-controlled, clinical study. Setting: Cardiology and postmenopausal outpatient clinics of a university hospital. Patient(s): Thirty postmenopausal women with hypertension (diastolic blood pressure of >90 mm Hg) and left ventricular diastolic dysfunction (mitral E/A ratio [the ratio of peak velocity of early mitral diastolic filling to late diastolic filling] of <1 and isovolumic relaxation time of >100 ms) were included in the study. Thirty normotensive postmenopausal women with normal left ventricular diastolic function served as the control group. Intervention(s): Conjugated equine estrogen (0.625 mg) was given orally. Left ventricular diastolic function was assessed by Doppler echocardiography at baseline and 3 hours after the administration of estrogen. Main Outcome Measure(s): Left ventricular diastolic filling as assessed by Doppler echocardiography. Result(s): Estrogen had no effect on heart rate or blood pressure in either study group. The baseline E/A ratios were 0.72 +/- 0.26 and 1.22 +/- 0.30, and the isovolumic relaxation times were 122 +/- 18 ms and 89 +/- ms in the hypertensive and normotensive groups, respectively. Estrogen had no significant effect on any of the Doppler parameters in the normotensive group. In the hypertensive group, there was a trend toward normalization of the E/A ratio (from 0.73 +/- 0.11 to 0.84 +/- 20) and a significant improvement in the isovolumic relaxation time (from 124 +/- 20 ms to 105 +/- 13 ms) in response to the administration of estrogen compared with placebo. Conclusion(s): A single dose of oral estrogen caused a significant improvement in left ventricular diastolic filling in hypertensive postmenopausal women with diastolic dysfunction. (Fertil Steril(R) 2000;73:66-71. (C) 1999 by American Society for Reproductive Medicine.)
Keywords: estrogen; diastolic dysfunction; postmenopausal women; DOPPLER-DERIVED PARAMETERS; HORMONE REPLACEMENT THERAPY; MENOPAUSE-INDUCED CHANGES; NORMAL SYSTOLIC FUNCTION; CORONARY HEART-DISEASE; AORTIC FLOW; CARDIOVASCULAR-DISEASE; SYSTEMIC HYPERTENSION; BLOOD-FLOW; FAILURE